Planetary Evaporation and the Dynamics of Planet Wind/Stellar Wind Bow Shocks. Issue Volume 10:Issue S314(2015) (November 2015) - Frank, A.; Lui, B.; Carroll-Nellenback, J.; Quillen, A. C.; Blackman, E. G.; Kasting, J.; Dobbs-Dixon, I.
Abstract: We present initial results of a new campaign of simulations focusing on the interaction of planetary winds with stellar environments using Adaptive Mesh Refinement methods. We have confirmed the results of Stone & Proga (2009) that an azimuthal flow structure is created in the planetary wind due to day/night temperatures differences. We show that a backflow towards the planet will occur with a strength that depends on the escape parameter. When a stellar outflow is included, we see unstable bow waves forming through the outflow's interaction with the planetary wind.